Stability of degenerate vortex states and multi-quanta confinement effects in a nanostructured superconductor with Kagome lattice of elongated antidots. (25th September 2018) - Xue, Cun; Ge, Jun-Yi; He, An; Zharinov, Vyacheslav S; Moshchalkov, Victor V; Zhou, You-He
Abstract: In the present work, we directly visualize the multi-quanta cages (MQCs) consisting of the giant vortices pinned by the elongated antidots using low-temperature scanning Hall probe microscopy. The periodic but sufficiently isolated MQCs, observed at various magnetic fields, are in a good agreement with the simulated vortex states based on the time-dependent Ginzburg–Landau (tdGL) equations. Due to the competition between the interstitial vortices and the pinned giant vortices, the formation and collapse of the MQCs can be tuned by varying magnetic field. The experimental statistics of the interstitial vortices confined in the MQCs show that the interstitial vortex patterns become more disordered at higher magnetic fields. The stability of the degenerate vortex states and the multi-quanta confinement effects under an external current are also investigated by using the tdGL simulations. The splitting of the free energy of the degenerate vortex states indicates that applying external current can eliminate parts of the degenerate vortex states.